EKOSISTEM RUMEN KAMBING YANG DIBERI KULIT BUAH KAKAO SETELAH ALKALISASI DENGAN KOH DAN BIOFERMENTASI DENGAN Saccharomyces cerevisiae - Padang, Padang (FAPETKAN UNTAD, 2011)
The Â experiment on cocoa-pod husk processing by soaking it in KOH solution and fermenting Â Â it with Saccharomyces sereviceae was conducted to study its effects on ruminal concentration of total VFA and ammonia in Kacang goat. The study was carried out with a 2x4 factorials randomized design. The first factor was soaking treatment (soaked in KOH solution or not soaked), while the second factor was 4 levels of Saccharomyces sereviceae concentrations (0, 5, 10, and 15%). Each treatment was repeated three times. Responses of soaking treatment on parameters observed were analyzed with a t test while those of Saccharomyces sereviceae levels were tested with a polynomial orthogonal test. Results indicated that there were no interactions between the soaking treatment and concentrationa of Saccharomyces sereviceae in affecting parameters observed. Concentrations of rumen VFA increased with increasing levels of Saccharomyces sereviceae. Soaking in KOH solution increased rumen fluid VFA concentration, but decreased that of rumen ammonia in Kacang goat